Phylogeographical Pattern and Population Evolution History of Indigenous Elymus sibiricus L. on Qinghai-Tibetan Plateau - Han, Mengli; Zhang, Jingxue; Li, Daxu; Sun, Shengnan; Zhang, Changbing; Zhang, Chuanjie; Yan, Lijun; Guan, Yongzhuo; Chen, Lili; Guo, Yuxia; You, Minghong; Gou, Wenlong; et al. (Frontiers in Plant Science, 2022)
Until now, there are no study on the evolutionary history and the phylogeographical pattern about spatial-temporal population dynamics of important Elymus species, which is widely distributed with important economic and ecological values as the dominant community species on the high cold grazing land of Qinghai-Tibetan Plateau (QTP). The goal of this study is to reveal the existing distribution pattern of Elymus sibiricus L. in the Qinghai-Tibet Plateau and and the causes of this distribution pattern. In this paper, we studied population genetic structure and demography history of 216 individuals from 44 E. sibiricus populations on the QTP based on specific-locus amplified fragment sequencing (SLAF-seq). We found there was no single genetic diversity center was observed across all the E. sibiricus populations. The results of genetic variation showed that 44 populations were clearly divided into three groups: Qinghai Plateau (Group Ⅰ), South Tibet (Group Ⅱ), Hengduan Moutain (Group Ⅲ). From the three analyses of AMOVA, Mantel test and Treemix, strong genetic differentiation across all populations and low genetic differentiation among populations within three groups were characteristic by the comprehensive isolation by distance (IBD) across the whole QTP and by local gene flow, respectively. Molecular dating indicated that E. sibiricus diverged at 46.38 Ma (about during the Mid-Eocene) when the QTP was just beginning to uplift during this period. It is speculated that the reasons affecting the current phylogeographical pattern are as follows: 1. environment changes due to the uplift of the QTP; 2. The geographic distance between the populations (Group Ⅰ and Group Ⅲ are close in geographic distance, and gene flow are frequent); 3. Geographical barriers (the Tanggula and Bayangela Mountains between Group Ⅰ and Group Ⅱ).